Chemical profiling, isolation, and characterization of bioactive compounds from Rhynchosia minima var prostrata and Phragmites mauritianus - October, Natasha (University of Pretoria, 2023)
Thesis (PhD (Chemistry))--University of Pretoria, 2022.